Enkephalin is essential for the molecular and behavioral expression of cocaine sensitization - Mongi Bragato, Bethania del Carmen (2014)
Behavioral sensitization to cocaine is associated to neuroadaptations that contribute to addiction. Enkephalin is highly expressed in mesocorticolimbic areas associated with cocaine-induced sensitization; however, their influence on cocaine-dependent behavioral and neuronal plasticity has not been explained. In this study, we employed a knockout (KO) model to investigate the contribution of enkephalin in cocaine-induced behavioral sensitization. Wild-type (WT) and proenkephalin KO mice were treated with cocaine once daily for 9 days to induce sensitization. Additionally, to clarify the observations in KO mice, the same procedure was applied in C57BL/6 mice, except that naloxone was administered before each cocaine injection. All animals received a cocaine challenge on days 15 and 21 of the treatment to evaluate the expression of locomotor sensitization. On day 21, microdialysis measures of accumbal extracellular dopamine, Western blotting for GluR1 AMPA receptor (AMPAR), phosphorylated ERK2 (pERK2), CREB (pCREB), TrKB (pTrkB) were performed in brain areas relevant for sensitization from KO and WT and/or naloxone- and vehicle pre-treated animals. We found that KO mice do not develop sensitization to the stimulating properties of cocaine on locomotor activity and on dopamine release in the nucleus accumbens (NAc). Furthermore, pivotal neuroadaptations such as the increase in pTrkB receptor, pERK/CREB and AMPAR related to sensitized responses were absent in the NAc from KO mice. Consistently, full abrogation of cocaine-induced behavioral and neuronal plasticity after naloxone pre-treatment was observed. We show for first time that the proenkephalin system is essential in regulating long-lasting pivotal neuroadaptations in the NAc underlying behavioral sensitization to cocaine.